Optimizing English Language Assessment through Multiple Intelligences and Local Wisdom Integration - Aditama, Madya; shofyana, maila huda (Universitas Muhammadiyah Jember, 2025)
This study explored the implementation of Multiple Intelligences (MI) based assessments integrated with local wisdom in the English language teaching context at SMP Muhammadiyah Tersono, under the Merdeka Curriculum. It is a qualitative phenomenological approach, data were gathered from two English teachers of grades 7 and 8 through participatory observations, in-depth interviews, and document analysis. Findings reveal that MI-based assessments enhance students' engagement and learning outcomes, particularly in logical-mathematical and interpersonal intelligences. The integration of local wisdom fosters a culturally relevant and meaningful learning experience, aligning with the curriculum's holistic education goals. However, challenges persist, including limited resources and varying teacher competencies in applying MI principles effectively. The study discovers the importance of continuous professional development for teachers to enhance their understanding and implementation of MI-based assessments. This research contributes to the body of knowledge on MI and culturally integrated education, providing practical insights for educators and policymakers. Future studies are recommended to explore broader applications and long-term impacts of MI-based assessments in diverse educational settings.